2022
DOI: 10.1186/s12868-022-00749-1
|View full text |Cite
|
Sign up to set email alerts
|

CXCL1/CXCR2 is involved in white matter injury in neonatal rats via the gut–brain axis

Abstract: Background This study aimed to investigate whether CXCL1/CXCR2 mediates intestinal injury or white matter injury by delivering inflammatory mediators through the gut–brain regulation axis. Methods Neonatal SD rats, regardless of sex, were administered 3% dextran sulfate sodium via intragastric administration at different time points to construct necrotizing enterocolitis (NEC) models. Meanwhile, hypoxia and ischemia were induced in 3 day-old SD rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
4
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 37 publications
(36 reference statements)
2
4
1
Order By: Relevance
“…We did not find a difference in NeuN-positive mature neurons in mice with enterocolitis versus controls (Figure 5). Our microglia and neuron results contrast with other groups, which found that NEC induction decreased mature neurons and increased microglia numbers in the hippocampus, basal ganglia, and cerebral cortex of pigs and mice [13,34,47]. However, these studies used different ages, induction protocols, and employed different animal species, where cell development and number may innately differ.…”
Section: Implications For the Gut-brain Axiscontrasting
confidence: 99%
See 3 more Smart Citations
“…We did not find a difference in NeuN-positive mature neurons in mice with enterocolitis versus controls (Figure 5). Our microglia and neuron results contrast with other groups, which found that NEC induction decreased mature neurons and increased microglia numbers in the hippocampus, basal ganglia, and cerebral cortex of pigs and mice [13,34,47]. However, these studies used different ages, induction protocols, and employed different animal species, where cell development and number may innately differ.…”
Section: Implications For the Gut-brain Axiscontrasting
confidence: 99%
“…Consistent with other groups [15, 34], DSS exposure in neonatal mice results in enterocolitis and, to a lesser extent, colitis (Figure 2A-C), which contrasts with DSS’s effects in adult mice [27]. Increased DSS supplementation resulted in worse macroscopic gut assessment scores (bowel distension, bloody stool, and friability), which correlates with NEC severity in other models [18].…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Another level of complexity arises from crosstalk between the brain and other organs. Several studies have reported on reciprocal interactions between the injured or diseased brain with the gut microbiome and how therapeutic drugs may influence these interactions [ 17 20 ]. Moreover, organ dysfunction has been recognized to be bidirectional, meaning that dysfunction in one organ potentiates injury to others.…”
mentioning
confidence: 99%